2013
DOI: 10.1179/2042618612y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

The relative effectiveness of segment specific level and non-specific level spinal joint mobilization on pain and range of motion: results of a systematic review and meta-analysis

Abstract: Study design: Systematic literature review and meta-analysis. Objective: In symptomatic subjects to: (1) examine the effects of a single session of joint mobilization on pain at rest and with most painful movement, and (2) compare the effects when joint mobilization is provided to a specific or non-specific spinal level. Background: Joint mobilization is routinely used for treating spinal pain in conjunction with other interventions, but its unique effect is not well understood. Further, there is controversy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
2
24
0
1
Order By: Relevance
“…Second, similar treatment effects have previously been shown to occur when a nonspecific level versus a specific level is treated with mobilizations in patients with mechanical neck pain. 1,39,40 However, this is the first study to investigate manual therapy mobilizations at a specific level and in a specific direction (direction targeting an increase of the IVF) in patients with CR. Third, the study was adequately powered for the primary outcome (NDI) but underpowered for several secondary outcomes.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Second, similar treatment effects have previously been shown to occur when a nonspecific level versus a specific level is treated with mobilizations in patients with mechanical neck pain. 1,39,40 However, this is the first study to investigate manual therapy mobilizations at a specific level and in a specific direction (direction targeting an increase of the IVF) in patients with CR. Third, the study was adequately powered for the primary outcome (NDI) but underpowered for several secondary outcomes.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Our approach was symptomatic level treated and not randomly chosen. Speci ic techniques are more effective than general techniques in cervical spine [27].…”
Section: Interventionmentioning
confidence: 99%
“…12,13 While these techniques are commonly taught in manual therapy education, their lack of validity and reliability has not gone unnoticed. [14][15][16][17][18][19][20][21][22] Some journal commentaries and editorials have suggested MTs move away from segment specific motion palpation altogether, [23][24][25] and correspondingly, some studies have found positive results using techniques that were designed to treat a spinal region, not a specific motion segment. [26][27][28][29][30][31][32] However, research that supports the use of regional techniques also often encourages the use of segmental motion palpation as part of the clinical decision-making process.…”
Section: -11mentioning
confidence: 99%